AN ISLAMIC PERSPECTIVE ON SUSTAINABLE DEVELOPMENT - Akram Rana, Muhammad (South Asian Journal of Religion and Philosophy (SAJRP), 2021)
Sustainable development meets the needs of the present without compromising the ability of further generations to meet their own needs. According to Islamic teachings, everything on earth was created for the service of human beings. Hence, Islam allows the consumption of the natural environment but forbids unnecessary destruction and endeavors to balance environmental protection with social and economic development. This paper will discuss sustainable development in the light of Islam with special reference to the challenges facing Pakistan.